Differential change of borderline personality disorder traits during dialectical behavior therapy for adolescents - Bürger, Arne; Fischer-Waldschmidt, Gloria; Parzer, Peter; Kaess, Michael (Journal of personality disorders, 2019)
Despite the expansion of treatment options for adults with borderline personality disorder (BPD), research on treatment options for adolescent BPD is scarce. The aim of this study was to investigate the impact of dialectical behavior therapy for adolescents (DBT-A) on the individual trait level as primary outcome; and the frequency of suicide attempts and nonsuicidal self-injury, self-reported BPD core pathology, and general psychopathology as secondary outcomes. Seventy-two adolescents (aged 12-17 years) with full- or subsyndromal BPD were treated with DBT-A (25 single sessions, 20 sessions of skills training), and 13 patients (18.1%) withdrew during treatment. From baseline to post-treatment, the number of BPD traits decreased significantly (p ≤ .001). All secondary outcomes decreased significantly as well (p ≤ .001). Results of this uncontrolled study suggest that beside self-harm, DBT-A may also have a beneficial impact on other features of BPD.